Reframing concussions, masculinity, and NFL mythology in League of Denial. (2nd January 2016) - Furness, Zack
ABSTRACT: This article explores how the PBS Frontline documentary League of Denial reframes the "concussion crisis" in three ways that contest the rationalization of injury and the normalization of violence in the hegemonic masculine discourses (visual, written, oral) produced about professional football. First, the film problematizes the notion of head injury as merely "part of the game" and a risk that players ostensibly understand when they enter the National Football League. Second, the film's depiction of Mike Webster's "unruly" body further de-naturalizes concussions and contests the masculine ideal of bodily sacrifice in pro football. Third, the film explicitly critiques the role of sports media in constructing a mythology and spectacle of pro football that contributed to the cultural context in which the concussion crisis has emerged.